Mn2O3 oxide with bixbyite structure for the electrochemical oxygen reduction reaction in alkaline media: Highly active if properly manipulated. (20th January 2021) - Ryabova, Anna S.; Istomin, Sergey Ya.; Dosaev, Kirill A.; Bonnefont, Antoine; Hadermann, Joke; Arkharova, Natalya A.; Orekhov, Anton S.; Sena, Robert Paria; Saveleva, Viktoriia A.; Kéranguéven, Gwénaëlle; Antipov, Evgeny V.; Savinova, Elena R.; et al.
Abstract: We consider compositional and structural factors which can affect the activity of bixbyite α-Mn2 O3 towards the oxygen reduction reaction (ORR) and the stability of this oxide in alkaline solution. We compare electrochemistry of undoped, Fe and Al-doped α-Mn2 O3 with bixbyite structure and braunite Mn7 SiO12 having bixbyite-related crystal structure, using the rotating disk electrode (RDE), the rotating ring-disk electrode (RRDE), and cyclic voltammetry (CV) techniques. All manganese oxides under study are stable in the potential range between the ORR onset and ca. 0.7 V vs. Reversible Hydrogen Electrode (RHE). It is found that any changes introduced in the bixbyite structure and/or composition of α-Mn2 O3 lead to an activity drop in both the oxygen reduction and hydrogen peroxide reactions in this potential interval. For the hydrogen peroxide reduction reaction these modifications also result in a change in the nature of the rate-determining step. The obtained results confirm that due to its unique crystalline structure undoped α-Mn2 O3 is the most ORR active (among currently available) Mn oxide catalyst and favor the assumption of the key role of the (111) surface of α-Mn2 O3 in the very high activity of this material towards the ORR.